COMPARATIVE STUDY: THE ANTIBACTERIAL ACTIVITY OF MELISSA IN RELATIONS TO OTHER PLANTS IN THE REGION OF SETIF, ALGERIA - Adimi L. Z.; Guechi A.; Laidoudi O.; Chelil S.; Kicheh I. (European Scientific Journal, ESJ, 2015)
Antibacterial properties of essential oils, hydro ethanoicextracts, and aqueous bactericidal extracts of four medical plants, known for their therapeutic effects: Melissa officinalis , Origanum vulgare , Lavandula angustifolia and Mentha piperita. The last three are largely used in Algeria; however, Melissa appears to be less famous. The following work has been executed in a laboratory for the purpose of, yet again, revealing and confirming the benefits of Melissa, and comparing it to other plants. Two microorganisms have been used: Escherichia coli and Staphylococcus aureus. Using the method of Aromatogram with essential oils, Melissa was active the most with zones of inhibition of 8 mm for Escherichia coli and 7 mm for Staphylococcus aureus. Applying the same method for hydro ethanoicextracts, Melissa was effective the most with a 50 mm zone of inhibition for Escherichia coli, followed by mint (40 mm zone of inhibition). As for Staphylococcus aureus, Melissa presented a 14 mm zone of inhibition, while mint displayed a zone of inhibition of 13 mm. Using the bioassay method with essential oils, Melissa has the best effect with a 40 mm zone of inhibition for Escherichia coli and 35mm for Staphylococcus aureus. Always with the same technique but with hydro ethanoicextracts, both Melissa and Mint presented the best inhibition value of 50 mm for Escherichia coli. As for Staphylococcus aureus, Melissa presented a 26 mm zone of inhibition, followed by mint with 24 mm. For the spectrophotometry technique, almost all four plants, witht heir aqueous extracts, presented a antibacterial activity for both bacteria. These results confirm the strong anti- bacterial and bactericidal activity of the four plants, especially Melissa, and their diverse traditional use.